Varieties of democracy and economic growth :|a panel data analysis - Akekmekçi, Özlem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
This thesis addresses the question how different democracy varieties affect the economic growth. For the varieties of democracy, the indices of V-Dem Institute are used and the democracies has categorized into five different groups as following: electoral, liberal, participatory, deliberative and egalitarian. With the fixed effect estimation of the regression with Driscoll-Kraay standard errors, panel data for 86 countries over the period from 1960 to 2016 is used. The findings imply that, economic growth have positive correlation with all democracy indices and strongest correlation is with egalitarian democracy. Since electoral democracy index act as basic essential of other democracy indices; add to regressions performed with these indices, the correlations of components without the partial score of electoral democracy index is also analyzed separately. Findings show that participatory, deliberative and egalitarian democracy components are not significant without the essential characteristics of any democracies. As control variables, geopolitical region, trade openness, life expectation and primary schooling are estimated as significant for all democracy variations. However, only for egalitarian democracy, ethnic fractionalization is insignificant in some circumstances. Also, the coefficient of ethnic fractionalization is lowest for the egalitarian democracy. This finding is supportive to following arguments in the literature, democratic regimes tend to manage ethnic fractionalization better and equal distribution has highly important role in this. In consideration of the literature and the findings, it may be said that equal distribution of power and resources likely to reduce the unfavorable effects of ethnic fractionalization on economic growth.
Keywords: Economic development.; Democracy.